A experiência turística inteligente e suas consequências sobre o viajante segundo a teoria do apego e a teoria das trocas sociais - Stela Cristina Hott Corrêa (2021)
The World Tourism Organization has encouraged the formation of smart tourism destinations (STDs). Their ecosystem maintains a network of connected organizations in favor of an environment favorable to the smart tourism experience (STE). This movement increased the STE research, however limited attention has been paid to the traveller's perception. Thus, the objective of this work is to validate the dimensions of the smart tourism experience and estimate its consequences for the traveler according to the social exchange theory. This research was guided by two methodological approaches. The one was the Grounded Theory, where two theoretical codes were elaborated for representing the substantive theoretical structures of the STE-STD and its consequences. The first of them, “living as a citizen”, reflects the perception of travelers, researchers and tourism professionals, both in the private and public sectors. The second, “smart tourism destination”, establishes the impressions of travelers, with and without disabilities, about STE. The respondents understand STE as an interactive experience, rich in digital accessibility and information and communication technology (ICT), which enables mobility, personalization of the experience, fun, sharing and searching for information in digital media. Trust, independence (dependence-power) and commitment (understood as place attachment), emerged as elements of social exchange that explain the relationships between the traveler and other stakeholders. In the second methodological course, the dimensions of the STE were validated and its consequences were tested by means of structural equation modeling. The data were collected internationally on the crowdsourcing platforms Prolific and Pollfish by performing two samples (initial and final). The direct impact of STE on the well-being, trust and independence were confirmed as well its indirect impact - via well-being - on place attachment and personal transformation. This result showed that in the STE there are the appropriate conditions for development of the place attachment, since through the STE, the traveler feels the belonging and the psychological connection to the STD seeing himself as part of it. This finding is unprecedented, because until then the place attachment had been studied in several other contexts, but not in the context of the STE and STD. Thus, the main theoretical contribution of this research is the introduction of attachment theory in the context of social exchanges by through the STE. In such a way the destination is the object of the traveler's attachment and the well-being is the agent by which the psychological bonds and sense of belonging are formed, that is, their attachment to STD. In addition, the research contributes to the studies of positive psychology by reconfirming the capacity of well-being to bring about the personal transformation of the traveler. Another contribution is the validation of scales for measuring constructs not yet measured as the STE's dimensions (ICT, digital accessibility, smart mobility, smart influence of third parties, data sharing, smart personalization of experiences and fun) and the traveller independence. These results indicate that tourism services supported by technology - notably those offered by individual microentrepreneurs - tend to be more personalized and socially interactive, favoring the place attachment, and therefore, they should be encouraged by Destination Marketing Organizations and policies public.